Systematic review and meta-analysis of randomized controlled trials of interventions addressing caregiver distress and burden among cancer caregivers - Trupti Dhumal; Zasim Azhar Siddiqui; George A. Kelley; Felicity Harper; Kimberly M. Kelly (Elsevier, 2023)
Objective: Informal caregivers (ICs) are vital to supportive cancer care and assisting cancer patients, but this caregiving burden is associated with significant distress. While addressing caregiving, it is important to explore if the caregivers are receiving care they need. Evaluating interventions that address burden and distress is integral to targeting ICs needs. This study evaluated interventions addressing IC burden and distress. Methods: Randomized control trials (RCT) assessing interventions for IC burden and distress and exploring supportive care as an adjunct to the intervention were included. Six electronic databases were searched in accordance with the Preferred Reporting Items for Systematic reviews and Meta-analyses guidelines through October 2021. Effect sizes were estimated, and risk of bias was assessed. Results: Of 678 studies, 11 were included. Most ICs were spouses, females, and white. Interventions included educational programs, cognitive behavioral treatment, and a telephone support program. Five studies utilized behavioral theories and seven included supportive care. Pooled results showed no significant effect on reducing caregiver distress (ES, -0.26, p<0.001). Conclusions: Caring for the caregiver with interventions for reducing burden and distress are not efficacious. Innovative, well-designed, more pragmatic RCTs are needed. Innovation: This study exclusively focused on interventions and supportive care needs for reducing distress and burden among cancer ICs.